Near complete genome sequence of the animal feed probiotic, Bacillus amyloliquefaciens H57. Issue 1 (December 2016) - Schofield, Benjamin; Skarshewski, Adam; Lachner, Nancy; Ouwerkerk, Diane; Klieve, Athol; Dart, Peter; Hugenholtz, Philip
Abstract Bacillus amyloliquefaciens H57 is a bacterium isolated from lucerne for its ability to prevent feed spoilage. Further interest developed when ruminants fed with H57-inoculated hay showed increased weight gain and nitrogen retention relative to controls, suggesting a probiotic effect. The near complete genome of H57 is ~3.96 Mb comprising 16 contigs. Within the genome there are 3, 836 protein coding genes, an estimated sixteen rRNA genes and 69 tRNA genes. H57 has the potential to synthesise four different lipopeptides and four polyketide compounds, which are known antimicrobials. This antimicrobial capacity may facilitate the observed probiotic effect.